METABOLIC AND CARDIOVASCULAR COMORBIDITIES IN BULGARIAN PATIENTS WITH CHRONIC VIRAL B AND C HEPATITIS - Radoslava Tsrancheva; Dimitar Stoyanov; Maria Stancheva; Rozita Karakasheva; Blagovest Stoimenov; Ralitsa Pancheva; Svilen Donev; Ventseslav Yordanov; Nikola Stanchev; Ventsislava Pencheva; Diana Stefanova-Petrova (Journal of IMAB)
Recent epidemiologic data on chronic viral B and C hepatitis in Bulgaria are limited.The evolution of these infections depends on liver complications and the presence of nonliver comorbidities. The aim of the study was to assess the frequencies of arterial hypertension, ischemic heart disease, myocardial infarction, chronic heart failure, type 2 diabetes mellitus and metabolic syndrome in patients with chronic viral B and C hepatitis, associated liver cirrhosis and to compare with those of uninfected controls. Material/Methods: We conducted a retrospective cross-sectional study in the period 2003-2023. We included 1803 patients, 474 with chronic hepatitis B, 482 with chronic hepatitis C and 847 uninfected controls. The patient's medical records were analyzed for the presence of arterial hypertension, ischemic heart disease, myocardial infarction, chronic heart failure, type 2 diabetes mellitus and metabolic syndrome. Results: The most common comorbidity in the three groups was arterial hypertension, followed by type 2 diabetes mellitus. The frequency increased in chronically infected patients with liver cirrhosis. We observed a higher prevalence of myocardial infarctions in the patients with chronic hepatitis C (p=0.045) and of metabolic syndrome in the hepatitis B group (p=0.028). A higher prevalence of ischemic heart disease was observed in the group with chronic hepatitis B and liver cirrhosis (p=0.01). Conclusions: Chronic hepatitis B and C in our groups were associated with significant morbidity, particularly with arterial hypertension and type 2 diabetes mellitus. The finding was more pronounced in patients with already developed liver cirrhosis.